Internalizing Quranic Values Through Arabic Language Teaching in Campus - Yusuf Efendi; Adi Hanif (Institut Studi Islam Muhammadiyah Pacitan, 2025)
This study aims to examine how the internalization of Qur’anic values can be achieved through Arabic language teaching in higher education. Arabic, as the language of the Qur’an, plays a strategic role not only as a means of communication but also as a medium for instilling moral, spiritual, and social values in students. The research method used was literature study and observation of the Arabic language learning process in the campus environment. The results show that the integration of Qur’anic values into Arabic language learning materials, such as through the selection of Qur’anic verses and the application of values-based teaching strategies, can increase spiritual awareness and character development in students. The role of lecturers as value mediators is crucial in facilitating this internalization process. Thus, Arabic language teaching in higher education not only develops language competence but also shapes students’ personalities with noble morals and based on the teachings of the Qur’an.